Poly(methyl methacrylate): Covalent Functionalization of PMMA Surface with L‐3, 4‐Dihydroxyphenylalanine (L‐DOPA) to Enhance its Biocompatibility and Adhesion to Corneal Tissue (Adv. Mater. Interfaces 1/2020). Issue 1 (10th January 2020) - Sharifi, Roholah; Mahmoudzadeh, Soudabe; Islam, Mohammad Mirazul; Koza, Darrell; Dohlman, Claes H.; Chodosh, James; Gonzalez‐Andrades, Miguel
Abstract : Poly(methyl methacrylate) (PMMA) surface is covalently functionalized with L‐3, 4‐dihydroxyphenylalanine (L‐DOPA) to form stable coating that significantly improves the biocompatibility of the PMMA. L‐DOPA‐functionalized PMMA also preserves the phenotypic characteristics of corneal fibroblast, supporting cellular adhesion, proliferation, and migration, which may lead to better biointegration of the Boston keratoprosthesis, the most commonly implanted artificial cornea for patients with severe corneal diseases. More details can be found in article number 1900767 by James Chodosh, Miguel Gonzalez‐Andrades, and co‐workers.